Dynamic adhesion forces between microparticles and substrates in water - Xu, Quan (Langmuir : the ACS journal of surfaces and colloids, 2014)
The interactions between micrometer-sized particles and substrates in aqueous environment are fundamental to numerous natural phenomena and industrial processes. Here we report a dynamically induced enhancement in adhesion interactions between microparticles and substrates immerged in water, air, and hexane. The dynamic adhesion force was measured by pulling microsized spheres off various substrate (hydrophilic/hydrophobic) surfaces at different retracting velocities. It was observed that when the pull-off velocity varies from 0.02 to 1500 μm/s, there is 100-200% increase in adhesion force in water while it has a 100% increase in nitrogen and hexane. The dynamic adhesion enhancement reduces with increasing effective contact angle defined by the average cosine of wetting angles of the substrates and the particles, and approaches the values measured in dry nitrogen and hexane as the effective contact angle is larger than 90(o). A dynamic model was developed to predict the adhesion forces resulting from this dynamic effect, and the predictions correlate well with the experimental results. The stronger dynamic adhesion enhancement in water is mainly attributed to electrical double layers and the restructuring of water in the contact area between particles and substrates